Freezing point temperature is in favor of not‐from‐concentrate apple juice storage - Gou, Xiaoju (Food Sci Nutr, 2019)
The short storage period is still a problem hindering the promotion of not‐from‐concentrate (NFC) apple juice, despite the fact it possesses higher nutritional value and more attractive taste compared with its concentrated counterparts. In this study, we compared the effects of temperature range including room temperature (25°C), refrigerator temperature (4°C), freezing point temperature (−1.5°C), and frozen temperature (−18°C), respectively, on the quality of NFC apple juices during a long storage period (150 days). The results suggested that all the juices exhibited good safety during the storage, and the juice stored at −1.5°C possessed higher polyphenol contents, physicochemical properties, less color alteration, and less loss of aroma and taste than 25 and 4°C. Besides, although an exceedingly low temperature (−18°C) could greatly retard the juice deterioration, the loss of aroma and taste was significant. Overall, our results indicated that the NFC juice was most favored by storage at freezing point temperature (−1.5°C), with the highest similarity to the freshly squeezed apple juice.